The Target Residence Time of Antihistamines Determines Their Antagonism of the G Protein-Coupled Histamine H1 Receptor - Bosma, Reggie; Witt, Gesa; Vaas, Lea A. I.; Josimovic, Ivana; Gribbon, Philip; Vischer, Henry F.; Gul, Sheraz; Leurs, Rob (Frontiers in Pharmacology, 2017)
The pharmacodynamics of drug-candidates is often optimized by metrics that describe target binding (Kd or Ki value) or target modulation (IC50). However, these metrics are determined at equilibrium conditions, and consequently information regarding the onset and offset of target engagement and modulation is lost. Drug-target residence time is a measure for the lifetime of the drug-target complex, which has recently been receiving considerable interest, as target residence time is shown to have prognostic value for the in vivo efficacy of several drugs. In this study, we have investigated the relation between the increased residence time of antihistamines at the histamine H1 receptor (H1R) and the duration of effective target-inhibition by these antagonists. Hela cells, endogenously expressing low levels of the H1R, were incubated with a series of antihistamines and dissociation was initiated by washing away the unbound antihistamines. Using a calcium-sensitive fluorescent dye and a label free, dynamic mass redistribution based assay, functional recovery of the H1R responsiveness was measured by stimulating the cells with histamine over time, and the recovery was quantified as the receptor recovery time. Using these assays, we determined that the receptor recovery time for a set of antihistamines differed more than 40-fold and was highly correlated to their H1R residence times, as determined with competitive radioligand binding experiments to the H1R in a cell homogenate. Thus, the receptor recovery time is proposed as a cell-based and physiologically relevant metric for the lead optimization of G protein-coupled receptor antagonists, like the H1R antagonists. Both, label-free or real-time, classical signaling assays allow an efficient and physiologically relevant determination of kinetic properties of drug molecules.